Stratigraphical and Sedimentological Review of the Merawu Formation, Serayu Basin, Central Jawa, Indonesia - Martosuwito, Surono; Bachri, Syaiful; Kamal, Zakiyah Ainul (Indonesian Journal on Geoscience, 2018)
DOI: 10.17014/ijog.5.2.117-128Merawu Formation is widely distributed in the Serayu Basin, Central Jawa, Indonesia. The formation is dominated by fine-grained clastic sediments comprising interbedded mudstone, siltstone, and sandstone. In the field, these outcrops are well exposed and well bedded. Stratigraphically, the Merawu Formation is underlain by the Paleocene Worawari Formation and overlain by the Late Miocene Penyatan Formation. Contacts between the Merawu Formation and the Worawari Formation are always found as fault types. Twelve sections have been done during the field work. Two members were identified within the Merawu Formation (Sandstone and Mudstone Members) in the field, where they interfinger each other. Previously, researchers interpreted the Merawu Formation as a turbidite sequence of deep marine deposits and depicted Early - Middle Miocene in age. However, the interpretation from the present research shows that the Merawu Formation was deposited on a tidal flat environment and has Early Miocene - Pliocene age, based on foraminifers found in some sections.